Monitoring the long term vegetation phenology change in Northeast China from 1982 to 2015. Issue 1 (December 2017) - Yu, Lingxue; Liu, Tingxiang; Bu, Kun; Yan, Fengqin; Yang, Jiuchun; Chang, Liping; Zhang, Shuwen
Abstract Global warming has contributed to the extension of the growing season in North Hemisphere. In this paper, we investigated the spatial characteristics of the date of the start of the season (SOS), the date of the end of the season (EOS) and the length of the season (LOS) and their change trends from 1982 to 2015 in Northeast China. Our results showed that there was a significant advance of SOS and a significant delay of EOS, especially in the north part of Northeast China. For the average change slope of EOS in the study area, the delay trend was 0.25 d/y, which was more obvious than the advance trend of −0.13 d/y from the SOS. In particular, the LOS of deciduous needleleaf forest (DNF) and grassland increased with a trend of 0.63 d/y and 0.66 d/y from 1982 to 2015, indicating the growth season increased 21.42 and 22.44 days in a 34-year period, respectively. However, few negative signals were detected nearby Hulun Lake, suggesting that the continuous climate warming in the future may bring no longer growing periods for the grass in the semiarid areas as the drought caused by climate warming may limit the vegetation growth.